The Folksong Narrative of the Family: Ritual Exposures and the Meaning of Shifting Contexts - Stundžienė, Bronė (Tautosakos darbai, 2016)
The article aims at outlining the framework of the family narrative based on folksongs perceived as profound texts of the ritual culture. The interpretation supported by hermeneutic assumptions seeks to reveal the aspects of the family life that are important to the poetic folksong discourse, as well as to establish the grounds for the reconstruction of the family narrative. The interest for the historical family patterns and the search for their possible reflections in folksongs was encouraged by the contemporary crisis experienced by the family institution. The “reading” of the songs was not a literal one, but rather, to paraphrase Gadamer, similar to a hermeneutic investigation, guided by the expectation of the universal meaning deduced from the total of singularities. The better understanding of the historic development of the family, its shifting structures and purposes required deeper knowledge of the linguistic kinship terms characterized by the ancient Indo-European roots, and the familiarity with the family rituals inseparable from the customary law still valid in the 16th century. It also involved noting changes in these phenomena that in turn affected the shifting notion of the family. This historically based information enabled the author to decipher the rather widely scattered ambiguous family reflections in the folksongs in a sufficiently objective way. The available linguistic research of the origins and spread of the Lithuanian kinship terms prompted paying attention to the rather numerous and revealing indications preserved by folksongs, testifying to their living memory of the extended family structure existing in Lithuania several centuries ago. The subsequent probing of the ritual memory of the Lithuanian folksongs involved placing it against the increasingly broader theoretically reconstructed ritual pattern. Recent studies of the Slavic family culture enabled establishing numerous ritual parallels with the Lithuanian (and the Baltic) one, as reflected in the folksongs. Although priority of the family issues in the folksongs was evident even before, the deeper look into the family theme allowed determining the role of the marriage not only as the supreme transition point of the human life, but also as an important change of the social status, which in the ritual culture involved the whole family, kin and even broader society. Such situation lasted in Lithuania much longer than elsewhere in Europe, since even at the turn of the 19th century the essentially illiterate oral Lithuanian culture sanctioned transferring the relevant experiences by means of the repeated rituals. The current interpretation was somewhat hindered by the thick accumulation of the cultural contexts concentrated in the folksong discourse, and even more cluttered by reflections of their change. However, the analysis enabled concluding that for the old folksongs only one family theme was truly relevant, namely, the establishing of the new family, which involved crucially important extension of the proximity of blood by marrying offspring of two families and acquiring new members in turn related as in-laws. Actually, the difference between the blood and the in-law relationship is the main thing to deal with for the whole briefly surveyed folksong narrative of the family. So far, the author of the article pays more attention to the family organization based on the proximity of blood, selecting the relevant information from the dissemination of the wedding ritual in the folksongs. Therefore, this article essentially presents investigation of only one part of the folksong family narrative. Further, the process of integration into the in-law family and the relevant symbolic constellations await examination.
Keywords: -